Possible risk factors for poor asthma control assessed in a cross-sectional population-based study from Telemark, Norway. - Regine Abrahamsen; Gølin Finckenhagen Gundersen; Martin Veel Svendsen; Geir Klepaker; Johny Kongerud; Anne Kristin Møller Fell (PLoS ONE, 2020)
This cross-sectional study of the general population of Telemark County, Norway, aimed to identify risk factors associated with poor asthma control as defined by the Asthma Control Test (ACT), and to determine the proportions of patients with poorly controlled asthma who had undergone spirometry, used asthma medication, or been examined by a pulmonary physician. In 2014-2015, the study recruited 326 subjects aged 16-50 years who had self-reported physician-diagnosed asthma and presence of respiratory symptoms during the previous 12 months. The clinical outcome measures were body mass index (BMI), forced vital capacity (FVC) and forced expiratory volume in one second (FEV1), fractional exhaled nitric oxide (FeNO), immunoglobulin E (IgE) in serum and serum C-reactive protein (CRP). An ACT score ≤ 19 was defined as poorly controlled asthma. Overall, 113 subjects (35%) reported poor asthma control. The odds ratios (ORs) and 95% confidence intervals (CIs) for factors associated with poorly controlled asthma were: self-reported occupational exposure to vapor, gas, dust, or fumes during the previous 12 months (OR 2.0; 95% CI 1.1-3.6), body mass index ≥ 30 kg/m2 (OR 2.2; 95% CI 1.2-4.1), female sex (OR 2.6; 95% CI 1.5-4.7), current smoking (OR 2.8; 95% CI 1.5-5.3), and past smoking (OR 2.3; 95% CI 1.3-4.0). Poor asthma control was also associated with reduced FEV1 after bronchodilation (β -3.6; 95% CI -7.0 to -0.2). Moreover, 13% of the participants with poor asthma control reported no use of asthma medication, 51% had not been assessed by a pulmonary physician, and 20% had never undergone spirometry. Because these data are cross-sectional, further studies assessing possible risk factors in general and objectively measured occupational exposure in particular are needed. However, our results suggest that there is room for improvement with regards to use of spirometry and pulmonary physician referrals when a patient's asthma is inadequately controlled.